PENGARUH KUALITAS PELAYANAN RESEPSIONIS TERHADAP KEPUASAN TAMU PADA HOTEL SIBAYAK INTERNASIONAL BERASTAGI - Olga Theolina Sitorus (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2018)
Currently the tourism industry is experiencing a very rapid development. The hotel includes business ventures in the tourism sector that emphasize the sale of services for the satisfaction of its customers. Based on theresults of the analysis of the effects od service quality on guest satisfaction it can be included that the results of the calculation of the “product moment” correlation obtained r value of 0,499 this indicates that the correlation index is quite strong between service quality and guest satisfaction, meaning that service quality affects quest satisfaction. Based on the calculation of the determinant coefficient t count compared to t H0 table of 5,18 while t table value of 1,66412 means the value of t account > t table value then is rejected with accepted means that the quality of servicehas a significant effet guest satisfaction. Based on the results of the determinant calculation obtained a determinant value of 25 % and this shows that as much as 25 % of the quality od service affects guest satisfaction. While the rest iaas much as 75 % which means that others factors influence guest satisfaction.